Accurate detection of soil microbial community responses to environmental change requires the use of multiple methods. (June 2022) - Osburn, Ernest D.; McBride, Steven G.; Kupper, Joseph V.; Nelson, Jim A.; McNear, David H.; McCulley, Rebecca L.; Barrett, J.E.
Abstract: Identifying general patterns in microbial community responses to global change factors remains a challenge in soil ecology, partially due to different methods used to characterize microbial communities among studies. In this study, we used DNA-based (qPCR, sequencing) and PLFA approaches to assess microbial responses to both land use change and drought-rewetting. Both methods detected microbial community responses to land use change but the drought-rewetting responses detected by the two methods were qualitatively different: PLFAs revealed clear effects of soil drying on microbial communities, which 16S sequencing did not. In contrast, sequencing revealed strong responses to rewetting, which PLFAs did not show. Further, PLFAs revealed a marked increase in fungal:bacterial (F:B) ratios following drought, which was not evident in our qPCR data. Overall, our results show that full elucidation of microbial community responses to global change will require the use of multiple methodological approaches. Highlights: PLFA and DNA analyses detected similar microbial responses to land use change. PLFA and DNA analysis revealed qualitatively different microbial drought responses. DNA methods are insensitive to factors that likely result in relic-DNA accumulation. QPCR fungal:bacterial ratios reflect bacterial community composition, not abundance.